2020
DOI: 10.1007/s40273-020-00971-x
|View full text |Cite
|
Sign up to set email alerts
|

Lenalidomide with Rituximab for Previously Treated Follicular Lymphoma and Marginal Zone Lymphoma: An Evidence Review Group Perspective of a NICE Single Technology Appraisal

Abstract: The National Institute for Health and Care Excellence (NICE) invited the manufacturer (Celgene) of lenalidomide (Revlimid ® ), as part of the Single Technology Appraisal (STA) process, to submit evidence for the clinical effectiveness and cost-effectiveness of lenalidomide in combination with rituximab (MabThera ® ), together referred to as R 2 , for the treatment of adults with treated follicular lymphoma (FL) or marginal zone l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…[ 24 ] The results of the pharmacoeconomic analysis showed that it was better clinical effectiveness and better cost-effectiveness for lenalidomide plus rituximab treating adults with follicular lymphoma or MZL lymphoma, compared with the conventional chemotherapy regimen such as R-CHOP/R-CVP. [ 25 ] Although these studies yielded some positive results, these studies did not pay attention to MALT lymphomas with light chain-restricted plasmacytic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 24 ] The results of the pharmacoeconomic analysis showed that it was better clinical effectiveness and better cost-effectiveness for lenalidomide plus rituximab treating adults with follicular lymphoma or MZL lymphoma, compared with the conventional chemotherapy regimen such as R-CHOP/R-CVP. [ 25 ] Although these studies yielded some positive results, these studies did not pay attention to MALT lymphomas with light chain-restricted plasmacytic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“… 94 In the AUGMENT trial, no difference in the global quality of life assessment between R2 and lenalidomide was reported at any timepoint. 95 Therefore, we recommend using lenalidomide with an anti-CD20 antibody whenever possible. For elderly patients who find frequent visits to an infusion center burdensome and desire all-oral regimens, we favor other options discussed below.…”
Section: Relapsed/refractory Diseasementioning
confidence: 99%
“…Patient-reported outcomes from the trial were analyzed for health-related quality of life, showing no clinically meaningful changes from baseline across the post-baseline assessments for either arm. 21 Among FL patients, the LR arm had higher two-year overall survival (OS) rates than the R-placebo arm (95% vs 86%, p=0.02). LR appeared to be superior to R-placebo in all FL patient subgroups analyzed, including the elderly and those judged to be unfit for cytotoxic chemotherapy.…”
Section: Lr Treatment For Fl - Trials On Previously Treated Patientsmentioning
confidence: 99%